455 A Novel Anti-sense LncRNA of CEBPA Inhibits Bovine Adipogenic Differentiation. (7th December 2018) - Du, M
Abstract: Long non-coding RNAs (lncRNAs) have been revealed to play key role in the adipogenesis. Recently, a number of lncRNAs have been identified in adipose tissue by RNA sequencing, however the function of these lncRNAs remains largely undefined. In this study, we identified a novel bovine lncRNA located on bovine chromosome 18. It spans approximately 4.25 kb on the genome, containing two exons and one intron. The transcript is about 2608 bp which is an anti-sense lncRNA of CCAAT/enhancer-binding protein α gene (CEBPA), the product of which is known to regulate adipogenesis. To investigate the potential role of this LncRNA in adipogenesis, we cloned the anti-sense lncRNA of CEBPA into the pcDNA3.1+ vector. Then the construct was transfected into the bovine stromal vascular fraction (SVF) cells. Six hours (h) after transfection, an adipogenic inducing medium was applied. After 48 h following transfection, cells were collected. Compared to the pcDNA3.1+ vector only transfection, anti-sense lncRNA of CEBPA was dramatically enhanced due to LncRNA plasmid transfection (P cattle, lncRNA, adipogenesis Key Words: